1980
DOI: 10.3382/ps.0590363
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Protein during the Pre-Breeder Period on Subsequent Reproductive Performance of Large White Turkeys

Abstract: Large White turkey breeders of a commercial variety were used to determine the effects of pre-breeder dietary protein, frequency of insemination, and semen volume on subsequent reproductive performance. Treatments included female dietary protein levels of 10, 12, 14, and 17% fed from 12 to 32 weeks of age and 10, 12, an 14% protein from 20 to 32 weeks of age; male dietary protein levels of 12 and 17% fed from 12 to 56 weeks of age; and artificial insemination (AI) treatments of a) .025 ml of semen at weekly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Furthermore, eggs from the 20 million sperm/AI group The hatch of fertile eggs for the 20, 50, and 100 million sperm/AI groups in Weeks 16 to 20 was 56.6, 72.6, and 67.0%, respectively, with the 20 million group being significantly lower than the other two. Although reduced hatchability has been reported previously for poor quality or stale spermatozoa, (Nalbandov and Card, 1943;Woodard et al, 1976;Meyer et al, 1980) closer inspection of the Weeks 16 to 20 data revealed EI-20 and LI-20 hatchability values of 65.7 and 47.6%, respectively. The similarity of EI-20 hatchability to that of the 50 and 100 million sperm/AI groups seems to indicate that the 18.1% reduction in hatchability observed in the LI-20 treatment when compared to its EI-20 counterpart may have been responsible for the overall reduction in hatchability of the LI treatments and the 20 million sperm/AI groups (Table 3).…”
Section: Resultsmentioning
confidence: 50%
“…Furthermore, eggs from the 20 million sperm/AI group The hatch of fertile eggs for the 20, 50, and 100 million sperm/AI groups in Weeks 16 to 20 was 56.6, 72.6, and 67.0%, respectively, with the 20 million group being significantly lower than the other two. Although reduced hatchability has been reported previously for poor quality or stale spermatozoa, (Nalbandov and Card, 1943;Woodard et al, 1976;Meyer et al, 1980) closer inspection of the Weeks 16 to 20 data revealed EI-20 and LI-20 hatchability values of 65.7 and 47.6%, respectively. The similarity of EI-20 hatchability to that of the 50 and 100 million sperm/AI groups seems to indicate that the 18.1% reduction in hatchability observed in the LI-20 treatment when compared to its EI-20 counterpart may have been responsible for the overall reduction in hatchability of the LI treatments and the 20 million sperm/AI groups (Table 3).…”
Section: Resultsmentioning
confidence: 50%